Bioequivalence of macitentan and tadalafil given as fixed‐dose combination or single‐component tablets in healthy subjects - Grill, Simon; Bruderer, Shirin; Sidharta, Patricia N.; Antonova, Mariya; Globig, Susanne; Carlson, James; Schultz, Armin; Csonka, Dénes (British journal of clinical pharmacology, 2020)
Aims To demonstrate the bioequivalence of macitentan/tadalafil fixed‐dose combination (FDC) tablets with single‐component tablets of macitentan and tadalafil in healthy subjects. Methods Studies AC‐077‐101 and AC‐077‐103 were single‐centre, open‐label, single‐dose, 2‐period, randomized, crossover Phase 1 studies conducted in healthy subjects. Two FDCs were investigated: FDC‐1 and FDC‐2 in Study AC‐077‐101 and FDC‐2 in Study AC‐077‐103. Both FDCs contained 10 mg/40 mg of macitentan/tadalafil and differed in excipients and coating materials used. In both studies, pharmacokinetic sampling over 216 hours was conducted, and pharmacokinetic parameters were derived using noncompartmental methods. Results Bioequivalence of macitentan, its active metabolite ACT‐132577, and tadalafil was established for FDC‐2 in both studies AC‐077‐101 and AC‐077‐103 in which tadalafil as a single component was sourced from the USA and EU, respectively, to fulfil regional regulatory requirements. The area under the plasma concentration–time curve and maximum plasma concentration with 90% confidence intervals of all components were entirely within the bioequivalence limits (0.8000–1.2500). No subject died and no serious adverse events were reported in either studies. Conclusion The FDC‐2 tablet containing 10 mg/40 mg of macitentan/tadalafil was bioequivalent to the free combination of 10 mg macitentan and 40 mg tadalafil (both US and EU sourced). Macitentan and tadalafil were well tolerated when administered as FDC or as a free combination.